Pengaruh Fasilitas Wisata dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Taman Hutan Raya Ir. H. Djuanda Bandung - Mohamad Ridwan; Erie Hidayat Sukriadi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2022)
This research is motivated by problems related to tourist facilities and service quality to the satisfaction of Tahura Visitors Ir. H. Juanda Bandung. So the purpose of this study is to find out whether there is an influence of tourist facilities on visitor satisfaction, service quality on visitor satisfaction, and how much influence tourist facilities and service quality have on visitor satisfaction at Tahura Bandung. The research method used is a quantitative research method with multiple linear regression analysis, while the data collection technique uses observation, questionnaires, as well as literature studies from various literatures both online and in books. The population of this study is the visitors of Tahura with a sample of 100 respondents using probability sampling method with random sampling technique. The results showed that the overall tourist facilities and service quality provided by Tahura Ir. H. Djuanda Bandung has not received a good response from respondents, the influence of tourist facilities and service quality on visitor satisfaction Tahura Ir. H. Juanda Bandung. Calculation results based on the coefficient of determination show that R2 has a very strong relationship between indicators of tourist facilities, service quality and visitor satisfaction, which is 43.1% while 56.9% is influenced by other factors not examined in this study such as destination image, price. and physical evidence. Meanwhile, the results of the simultaneous test show that tourism facilities and service quality simultaneously (simultaneously) affect visitor satisfaction.